Antarctic Krill Oil Diet Protects against Lipopolysaccharide-Induced Oxidative Stress, Neuroinflammation and Cognitive Impairment - Ji Choi; Jun Jang; Dong Son; Hyung-Sik Im; Ji Kim; Joung Park; Won Choi; Sang-Bae Han; Jin Hong (International Journal of Molecular Sciences, 2017)
Oxidative stress and neuroinflammation are implicated in the development and pathogenesis of Alzheimer’s disease (AD). Here, we investigated the anti-inflammatory and antioxidative effects of krill oil. Oil from Euphausia superba (Antarctic krill), an Antarctic marine species, is rich in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). We examined whether krill oil diet (80 mg/kg/day for one month) prevents amyloidogenesis and cognitive impairment induced by intraperitoneal lipopolysaccharide (LPS) (250 µg/kg, seven times daily) injections in AD mice model and found that krill oil treatment inhibited the LPS-induced memory loss. We also found that krill oil treatment inhibited the LPS-induced expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) and decreased reactive oxygen species (ROS) and malondialdehyde levels. Krill oil also suppresses IκB degradation as well as p50 and p65 translocation into the nuclei of LPS-injected mice brain cells. In association with the inhibitory effect on neuroinflammation and oxidative stress, krill oil suppressed amyloid beta (1–42) peptide generation by the down-regulating APP and BACE1 expression in vivo. We found that eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) (50 and 100 µM) dose-dependently decreased LPS-induced nitric oxide and ROS generation, and COX-2 and iNOS expression as well as nuclear factor-κB activity in cultured microglial BV-2 cells. These results suggest that krill oil ameliorated impairment via anti-inflammatory, antioxidative, and anti-amyloidogenic mechanisms.